Numerical and Experimental Studies of Cavitation Behavior in Water-Jet Cavitation Peening Processing - H. Zhang; B. Han; X.G. Yu; D.Y. Ju (Shock and Vibration)
Water-jet cavitation peening (WCP) is a new technology for the surface modification of metallic materials. The cavitation behavior in this process involves complex and changeable physics phenomena, such as high speed, high pressure, multiple phases, phase transition, turbulence, and unstable features. Thus, the cavitation behavior and impact-pressure distribution in WCP have always been key problems in this field. Numerous factors affect the occurrence of cavitation. These factors include flow-boundary conditions, absolute pressure, flow velocity, flow viscosity, surface tension, and so on. Among these factors, pressure and vapor fraction are the most significant. Numerical simulations are performed to determine the flow-field characteristics of both inside and outside the cavitating nozzle of a submerged water jet. The factors that influence the cavitation intensity of pressure are simulated. Fujifilm pressure-sensitive paper is used to measure the distribution of impact pressure along the jet direction during the WCP process. The results show that submerged cavitation jets can induce cavitation both inside and outside a conical nozzle and a convergent-divergent nozzle when the inlet pressure is 32 MPa. Moreover, the shock wave pressure induced by the collapse of the bubble group reaches up to 300 MPa.